A Holistic Ecosystem Model to Diversify the Physician Workforce and Enhance Health - Erik J. Porfeli; Sunny Nakae; Leila Amiri; Leila E. Harrison; Will Ross (Health Equity)
Importance: The U.S. medical education system attracts and trains the next generation of physicians to advance the health care needs of a growing and increasingly diverse nation. This system can be credited for supplying a physician workforce achieving remarkable growth and innovation, yielding one of the world’s most technologically advanced health care systems on the planet. This system, unfortunately, also contributes to educational, workforce, and health disparities. Observations: The successes and challenges of the medical education and health care system align with broader economic, health, and educational patterns in the United States. An ecological model can be employed to unite a network of partners spanning four developmental stages to support a greater diversity of students for and from underrepresented communities to enter the physician workforce, enjoy the rewards granted by a career in medicine, and enact needed changes to eliminate health, economic, and educational disparities. Conclusions and Relevance: Comprehensive and ecologically attuned pathways to the physician workforce could be especially beneficial to states and communities suffering from the looming high school enrollment cliff, outflows of residents to other states, challenges in recruiting and retaining physicians, and significant educational and health disparities. The ecosystem model spurs significant changes in how we think about the developmental pathways to the physician workforce and how we may mobilize resources to promote progress and ease transitions, especially for underrepresented students who face many fewer opportunities and many more challenges along their journey.